Preventive interventions for diabetic foot ulcer adopted in different healthcare settings: A scoping review protocol. - Açucena Leal de Araújo; Francisca Diana da Silva Negreiros; Raquel Sampaio Florêncio; Thiago Dos Santos Garces; Virna Ribeiro Feitosa Cestari; Samuel Miranda Mattos; Samara Jesus Sena Marques; Francisca Eridan Fonteles Albuquerque; Wánderson Cássio Oliveira Araújo; Vanessa de Brito Poveda; Thereza Maria Magalhães Moreira (PLoS ONE)
Background Diabetic foot ulcers are challenging to heal, increase the risk of lower extremity amputation, and place a significant burden on patients, families, and healthcare systems. Prioritizing preventive interventions holds the promise of reducing patient suffering, lowering costs, and improving quality of life. This study describes a scoping review protocol that will be used to delineate the preventive interventions for diabetic foot ulcers employed in different healthcare settings. Methods The scoping review methodology was formulated in accordance with the PRISMA extension guidelines for scoping reviews and informed by the procedural insights provided by the JBI methodology group. Studies with participants diagnosed with type 1 and type 2 diabetes, aged 18 years or older, without an active ulcer at baseline, and studies of preventive interventions for foot ulcers in various healthcare settings will be screened. The search strategy was developed in collaboration with a research librarian using the PRESS checklist and no time or language limitations were applied. Data will be analyzed and summarized descriptively, including characteristics of studies, participants, and interventions. Discussion Understanding the strategies and gaps in diabetic foot ulcer prevention is critical. The literature can provide valuable insights for developing tailored interventions and strategies to effectively address these gaps, potentially accelerating progress toward improved outcomes in diabetic foot ulcer prevention. Review registration Open Science Framework DOI 10.17605/OSF.IO/FRZ97 [June 19, 2023].